2008
DOI: 10.1159/000131110
|View full text |Cite
|
Sign up to set email alerts
|

GABA and Histamine Interaction in the Basolateral Amygdala of Rats in the Plus-Maze Test of Anxiety-Like Behaviors

Abstract: In the present study, we have investigated the effects and the interaction of the GABAergic and histaminergic systems in the basolateral amygdala (BLA) of rats using the plus-maze test of anxiety-like behaviors. Unilateral injection of different doses of muscimol (GABAA receptor selective agonist; 0.01, 0.05 and 0.1 µg/rat) into the BLA (intra-BLA) increased the percentage of open arm time (%OAT) and open arm entries (%OAE) at the doses of 0.05 and 0.1 µg/rat that are representative of an anxiolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…In agreement with our data regarding anxiolytic effect of muscimol, it had been reported that intra-amygdala injection of the drug increased the percentage of open arm time and open arm entries [28], decreased duration of tonic immobility in guinea pigs [36] and produced anxiolytic-like effects in the social interaction test [29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our data regarding anxiolytic effect of muscimol, it had been reported that intra-amygdala injection of the drug increased the percentage of open arm time and open arm entries [28], decreased duration of tonic immobility in guinea pigs [36] and produced anxiolytic-like effects in the social interaction test [29].…”
Section: Discussionsupporting
confidence: 93%
“…Muscimol hydrobromid (SIGMA) was dissolved in 0.9% saline. Mean muscimol dose leading to anxiolytic-like effect was based on the literature data [28]. Muscimol (0.1 µg/0.5 µl, SIGMA) or saline (control, 0.5 µl) was injected into the right or left basolateral amygdala of HA and LA rats over 2 min.…”
Section: Stereotaxic Surgery and Microinjectionsmentioning
confidence: 99%
“…Subsequently, Loscher et al showed that GABAergic-rich LGE cell suspension grafts are capable of increasing afterdischarge threshold and decreasing seizure duration and severity in kindled epilepsy [24]. It appears that just as GABAergic grafts attenuated epileptiform activity in a similar manner as infusion of GABA agonists into seizure foci [6, 23], so too have engrafted GABAergic neurons attenuated contextual fear in a similar manner as infusion of GABA agonist within the amygdala [13, 29, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, excitability of the principal BLA neurons is regulated by these GABAergic neurons [14-18]. Thus, PV-positive neurons are critical for the expression of anxiety-like behavior since activation of PV-positive neurons and pharmacological stimulation of the GABAergic neuronal system in BLA can decrease emotional arousal and anxiety-like behavior [7,19,20]. …”
Section: Introductionmentioning
confidence: 99%